2007
DOI: 10.1126/stke.3942007jc1
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide: From Embryos to Tumors

Abstract: Ceramides are ubiquitous lipids that have important functions integral to apoptotic signaling. Several therapeutic agents currently exist that induce ceramide-dependent apoptosis in cancerous cells, and a number of enzymes involved in ceramide metabolism are beginning to be recognized as potential targets for cancer therapy. Recent research shows that evasion of ceramide-dependent apoptosis is essential at the earliest stages of embryonic development and is an important mechanism of multidrug resistance. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Thus, inhibition of AC might restore the sensitivity of cancer cells to exogenous ceramides or treatment with chemotherapeutic agents known to produce ceramide (24). Current techniques for AC inhibition are based on using ceramide analogs as inhibitors or anti-AC small interfering RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inhibition of AC might restore the sensitivity of cancer cells to exogenous ceramides or treatment with chemotherapeutic agents known to produce ceramide (24). Current techniques for AC inhibition are based on using ceramide analogs as inhibitors or anti-AC small interfering RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide may also form membrane channels for proteins like cytochrome C, and stabilize membrane rafts (42). The early embryo is resistant to apoptosis, owing to low levels of ceramide (43,44); however, there has been no measurement of ceramide during fertilization.…”
Section: Lipid Signaling Related To Fertilizationmentioning
confidence: 99%
“…The early embryo is resistant to ceramide-induced apoptosis (42), so ceramide presumably would have functions other than induction of apoptosis. Ceramide stabilizes membrane rafts (79) and alters PKC activity (59,80).…”
Section: Sm and Ceramidementioning
confidence: 99%
“…Ceramide, the central molecule of sphingolipid metabolism, generally mediates anti-proliferative responses, such as inhibition of cell growth, induction of apoptosis and/or modulation of senescence (Saddoughi et al , 2008). Several therapeutic agents that induce ceramide-dependent apoptosis in cancerous cells currently exist, and a number of enzymes involved in ceramide metabolism are beginning to be recognised as potential targets for cancer therapy (Savtchouk et al , 2007; Carpinteiro et al , 2008). Recent research has shown that cannabinoids induce ceramide accumulation in cancer cells, which is related to the pro-apoptotic effect of cannabinoids in cancer cells (Guzman et al , 2001; Velasco et al , 2005).…”
mentioning
confidence: 99%